Mulheres portadoras de papiloma vírus humano: uma revisão integrativa da literatura - COSTA, Priscila Rodrigues Alvão da (2019)
Integrative review aimed tosyn the size the scientific publications in national journalso nursing profile in women with human papillomavirus which is considered the main risk factor for the development of malignant lesion sin the uterine cervix. We conducted a literature review which included English language articles published between the years 2001to 2011. The sources were consulted Medical Literature AnalysisRetrieval System Online (Medline), Latin American Caribbean Health Sciences (LILACS), and Virtual Health Library (VHLBireme). For the three search descriptors were defined: Human Papillomavirus, Women and Socioeconomic profile. The final sample were 16 scientific productions that have addressed the issue at hand. Concluded that national surveys on this topic are stilling satisfactory compare dwith the relevance of the study.